2008
DOI: 10.1007/s11355-008-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbon content of soil in urban parks in Tokyo, Japan

Abstract: Because of difficulties in estimating the carbon fixation rate, we alternatively investigated the C content of the soil in 19 urban parks in the Tokyo metropolitan area. The C content of the soil under three vegetation types was measured: grassland/turf (''turf''); tree-planting area with plant management (with weeding and removal of fallen leaves) (''tree-planting area''); coppice or tree-planting area without plant management (''coppice''); bare land was used as control. Average C contents of turf, tree-plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 2 publications
1
11
0
1
Order By: Relevance
“…Related to the primary objective, this study aims at developing practical urban greening methods based on relevant concepts as well as exemplary practices: (a) the benefits of urban greening could be maximized by revamping entrenched thinking, practices and inertia; (b) decision makers could move from the conventional to the innovative mode, and adopt an integrated and long-term approach; (c) the entire cradleto-grave spectrum of urban greening demands attention, encompassing plantable sites, planning, design, species assemblage, installation, maintenance, management, governance, and community expectations (Attorre et al 2000;Jim and Chen 2006a); (d) notable gaps in knowledge have been identified for proposed improvement, such as the contribution to regional biodiversity and carbon sequestration (Takahashi et al 2008), and landscape and conservation planning (Jim and Chen 2009a, b); and (e) the framework could provide hints on future research priorities to strengthen the locally-relevant knowledge base and appropriate technology, and to inform management.…”
mentioning
confidence: 99%
“…Related to the primary objective, this study aims at developing practical urban greening methods based on relevant concepts as well as exemplary practices: (a) the benefits of urban greening could be maximized by revamping entrenched thinking, practices and inertia; (b) decision makers could move from the conventional to the innovative mode, and adopt an integrated and long-term approach; (c) the entire cradleto-grave spectrum of urban greening demands attention, encompassing plantable sites, planning, design, species assemblage, installation, maintenance, management, governance, and community expectations (Attorre et al 2000;Jim and Chen 2006a); (d) notable gaps in knowledge have been identified for proposed improvement, such as the contribution to regional biodiversity and carbon sequestration (Takahashi et al 2008), and landscape and conservation planning (Jim and Chen 2009a, b); and (e) the framework could provide hints on future research priorities to strengthen the locally-relevant knowledge base and appropriate technology, and to inform management.…”
mentioning
confidence: 99%
“…For instance, area-based total C densities of urban soils at 30-cm depths are reported to be 8.2 kg¨C¨m´2 for turf and 7.9 kg¨C¨m´2 for tree-planted areas in urban parks of Tokyo, Japan [21], 7.3 kg¨C¨m´2 for urban lawns in Fort Collins, USA [37], 5.0-17.2 kg¨C¨m´2 for golf courses in Melbourne, Australia [38], and 4.9-17.5 kg¨C¨m´2 for UGS's and urban forests in Auckland, New Zealand [22,39]. These values are much higher than the range of C densities, also at 30-cm depths, found in this study (1.55-3.02 kg¨C¨m´2; Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Because land use, land cover change, and/or urbanization history can all affect UGS soil C [17,[20][21][22], soil C densities in different types of UGS's such as roadside, park, school forest, and riverside were quantified and then compared to vegetation C density and site history. In addition, we reviewed the management of soil C in UGS's to enhance the ecosystem services of C storage.…”
Section: Introductionmentioning
confidence: 99%
“…(2005) reported that the soil carbon accumulation rate in man−made forests is 0.44 to 1.33 MgC ha yr. Takahashi et al . (2008) reported that the carbon accumulation rate of urban park soils is comparable to, or higher than, that associated with trees in parks (55 MgC ha yr).…”
Section: Murayama Katsuyamentioning
confidence: 99%